High Leptin and Low Adiponectin Levels in The Metabolic Syndrome Patients with Malignancy - Ria Ambarwati; Damai Santosa; Eko Adhi Pangarsa; Budi Setiawan; Mika Lumban Tobing; Muchlis Achsan Udji Sofro; Dharminto Dharminto; Tjokorda Gde Dalem Pemayun; Catharina Suharti (The Prodia Education and Research Institute (PERI), 2023)
BACKGROUND: Metabolic syndrome (MetS), which is characterized by insulin resistance, adipocyte accumulation, and obesity, has been linked to malignancy development. Both leptin, an adipose tissue-produced cytokine-like hormone, and adiponectin, a hormone secreted by adipose tissue, play roles in the progression of MetS. However, the presence of leptin and adiponectin is also assumed to be associated with cancer proliferation. Therefore, it is necessary to investigate the profile of leptin and adiponectin levels in MetS patients with malignancy and non-malignancy.METHODS: This was a cross-sectional study involving 80 MetS subjects with and without malignancy. Leptin and adiponectin levels of subjects were analyzed by using the enzyme-linked immunosorbent assay (ELISA) method. Mann-Whitney tests were used to compare leptin and adiponectin levels between groups.RESULTS: Leptin levels were significantly higher in MetS patients with malignancy (32.99±22.47 ng/mL) than those without malignancy (6.17±7.46 ng/mL). Conversely, adiponectin levels were lower in the malignancy group (10.11±7.66 µg/mL) compared to the non-malignancy group (13.44±8.29 µg/mL), with both differences being statistically significant (p<0.001 for leptin, p=0.023 for adiponectin).CONCLUSION: Leptin levels were found to be higher while adiponectin levels were found to be lower in MetS patients with malignancy compared to those without malignancy. Therefore, it is suggested that leptin and adiponectin levels might be used as malignancy markers in MetS patients.KEYWORDS: adiponectin, leptin, metabolic syndrome, malignancy